Trailblazing Sustainability: Lessons from University Efforts so Far - Petrović, Nataša; Jednak, Sandra; Andreja Radaković, Jelena; Ćirović, Marko; Savić, Dušan (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
Universities are pivots not only of knowledge but also of their practices, which must be sustainable in an age of environmental crisis and thus set an example for others because the academy has always been a beacon and guide, even in the most difficult times. Universities should also educate and "shape" the students who will be our future and the decision-makers who will impact us all. Bearing this in mind, the authors of the paper have decided to outline the examples of beneficial sustainable practices of the universities with special reference to the sustainable mobility practices of university students and employees because of their impact in the fight against climate change. In this way, the existing practices, as case studies that can be applied outside the institutions where they started, pave the way for other universities to include the improvement of sustainability as a necessary goal in their strategies.